C-band Dual-Polarization Radar Observations of a Massive Volcanic Eruption in South America - Vidal, Luciano (2017)
The eruption of Calbuco volcano on April 22-23, 2015 is the first volcanic eruption detected by a weather radar in South America. The detection was performed by the first domestically produced Argentinean weather radar, called RMA0 and located at Bariloche International Airport. It is a C-band Doppler dual-polarization system, manufactured by INVAP S.E. as a part of the new radar network of Argentina. The aim of this study is to present analysis of the time evolution of the structure of the volcanic plume using polarimetric observables. In order to explore the potential of this new data set for the analysis of the Calbuco volcano eruption column and dispersed ash cloud, synthetic backscattering signatures at C-band have been simulated and used to set up a threshold-based algorithm for tephra-type classification. An evaluation of lightning activity and its relationships with the volcanic particle spatial distribution and attendant polarimetric radar signatures are also discussed.